Flavonoids Production Capability Test of Tea Mistletoe (Scurrula atropurpurea BL . Dans) Endophytic Bacteria Isolates - Priyanto, Jepri Agung; Pujiyanto, Sri; Rukmi, Isworo (JURNAL SAINS DAN MATEMATIKA, 2014)
Tea Mistletoe (S. Atropurpurea BL. Dans) is a medicinal plant species used as anticancer because it contains some flavonoids compounds are chalcones, c-glycoflavonols, chatechin and quercetin. The ability of endophytic bacteria to produce similar bioactive compounds with its host plant is potential source to get flavonoids compounds. This research aims to know ability of endophytic bacteria in produce flavonoids compounds in vitro. Each isolate was fermented in submerged culture with 0.1% soluble starch, 0.5% pepton, and 0.15% yeast extract medium for 5 days, then extracted with ethyl acetate. Flavonoid content of the extract then was tested qualitatively and confirmation test used thin layer chromatography. Qualitative test results showed that crude extract from isolates B4, B5, B10, B17, and B19 positive containing flavonoids. The most potent extract were B10 and B19 tested by thin layer chromatography. Two of these extracts had the same Rf value with quercetin, thus endophytic bacteria from tea mistletoe can produce flavonoids in vitro.